Next Generation of Radio Spectrum Management: Licensed Shared Access and the trade-off between Static and Dynamic Efficiency - Maria Massaro; Gérard Pogorel; Erik Bohlin (International Telecommunications Society (ITS), 2015)
Increasing demand for access to the radio spectrum is setting the stage for a revision of existing radio spectrum management practices, mainly oriented towards exclusive use of frequency bands. A new wave of policy reforms is envisaged, with a potential shift of policy focus from static to dynamic efficiency. A previous wave of policy reforms promoted the implementation of market mechanisms for a more efficient distribution and use of radio frequencies, i.e. static efficiency. This second wave of spectrum policy reforms might translate into a new generation of spectrum management more centred on spectrum sharing solutions. Spectrum sharing could ensure more flexibility in spectrum use and certainty of radio spectrum access thanks to technology advances, thus promoting investment and innovation, i.e. dynamic efficiency. Among several forms of spectrum sharing solutions, collectively referred to as Dynamic Spectrum Access (DSA) systems, the concept of Licensed Shared Access (LSA) has recently been under scrutiny, in particular in the European Union (EU) and in the United States (US). LSA is an authorisation scheme that allows for shared use of already assigned but underused spectrum bands between incumbent(s) and new user(s) by means of exclusive individual spectrum rights of use. The adoption of the LSA regime would contribute to spectrum efficiency by making underused spectrum bands available for new users. The use of Reconfigurable Radio System (RRS) technologies, such as Software Defined Radio (SDR) and Cognitive Radio (CR) would minimise the risk of harmful interference. Against this background, this paper is intended as a progress report on the discussion upon the LSA regime, based on an extensive bibliography, which includes official documents, academic papers, position papers and reports. Several studies agree on the contribution LSA could bring in terms of spectrum efficiency. In this regard, selected elements of the LSA regime are assessed in terms of potential contribution to dynamic efficiency, taking into consideration the dichotomy between static and dynamic efficiency. These elements are: contract length; sharing arrangements; assignment procedure for LSA licences; implementation of RRS technologies; monitoring and enforcement. Although priority has historically been given to exclusive assignment of radio spectrum rights of use, the authors recognise the potential of LSA as a complementary regime that could promote spectrum efficiency. However, the authors advocate further exploration to clarify whether and to what extent LSA would be beneficial in terms of dynamic efficiency, i.e. promotion of investment and innovation and, thus, economic growth, taking into consideration the potential trade-off between static and dynamic efficiency.
Keywords: 330; Licensed Shared Access; spectrum sharing; static efficiency; dynamic efficiency